Herbal Formulations as Lepa (External Application) in Vyanga - A Review - Aswathi. N,; Jyolsna. G. Krishna, (International Journal of Ayurveda and Pharma Research, 2021)
Vyanga is one of the Kshudra roga (minor disorder), characterized by the presence of Niruja (painless), Tanu (light) and Shyava varna mandala (bluish black patches) on face. It is one of the most common diseases as regards the face is concerned. Description of the disease Vyanga is available from Samhita kala onwards. Most of the Aacharya have mentioned Vyanga in the chapter of Kshudra Roga. According to Charaka, Vyanga is said to be manifested by the suppression of Chardi vega. The aggravated Vata and Pitta along with Rakta are responsible for its manifestation. The Manasika nidana like Soka, Krodha and Ayasa are also result in the disease Vyanga. The Ayurvedic management of Vyanga includes both Sodhana and Samana chikitsa and Samana comprises of both internal and external medications. As the disease is mainly concerned with the skin, external applications like Lepa is having a prime importance here. Drugs with Rakta prasadaka (blood purifying), Twachya (conducive to skin) and Varnya (improving complexion) properties are commonly used in the management of Vyanga. They help to pacify aggravated Vata & Pitta dosha, thus aid in disease cure. Here it is tried to include some of the simple herbal formulations as Lepa (external application) mentioned in Ayurvedic texts for the management of Vyanga.